2009 9th International Conference on Telecommunication in Modern Satellite, Cable, and Broadcasting Services 2009
DOI: 10.1109/telsks.2009.5339454
|View full text |Cite
|
Sign up to set email alerts
|

Highly pure signal generators

Abstract: The special testing signal generators were designed for a series of frequencies in the frequency band 0.5 to 20 MHz. The generator is very simple. It is composed of only one stable crystal oscillator and one high power amplifier. The frequency stability of the generators is in the order of 10 -6 /day, the output power is 1W, the value of SINAD is under -130 dB and the total harmonic distortion is under -170 dB by using a linear narrowband filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The evaluation of the harmonic content in electronic oscillators is a very old problem [1-2], which has not lost importance until now [3]. Many mathematical methods of the nonlinear oscillations analysis were created (an excellent review of the early work can be found in [4]), and the work is still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the harmonic content in electronic oscillators is a very old problem [1-2], which has not lost importance until now [3]. Many mathematical methods of the nonlinear oscillations analysis were created (an excellent review of the early work can be found in [4]), and the work is still ongoing.…”
Section: Introductionmentioning
confidence: 99%